NURSING AND INTERNATIONAL SAFETY GOALS: HEMODIALYSIS ASSESSMENT - Letícia Lima Aguiar; Maria Vilani Cavalcante Guedes; Roberta Meneses Oliveira; Ilse Maria Tigre de Arruda Leitão; Viviane Peixoto dos Santos Pennafort; Ariane Alves Barros (Universidade Federal do Paraná, 2017)
The objective of this study was to describe the nursing care offered at a hemodialysis hospital service based on international patient safety goals. A descriptive study was conducted at the hemodialysis service of a Brazilian public hospital, reference in care for acute and chronic kidney patients, between August and October, 2013. Twenty-five nursing professionals participated in the study. Data were collected through interviews, observation and a checklist based on the safety goals of the Joint Commission International. The goals found to be in conformity were: improving effective communication; reducing the risk of healthcare-associated infections; and reducing the risk of patient harm resulting from falls. The remaining goals, namely: identifying patients correctly; improving the safety of high-alert medications; and ensuring safe surgery, deserve attention from the researched team and the assessed institution. The research found a need for the implementation of protocols in the service aimed at patient and team safety.